An assessment of whale watching impacts on the behaviour of humpback whales (Megaptera novaeangliae) in Skjálfandi Bay, Iceland - Vatcher, Hanna, 1993- (2020)
Whale watching has become a billion-dollar industry around the world that provides employment and economic benefits to communities and nations. In Northeast Iceland, a small town on Skjálfandi Bay has established itself as the whale watching capital of Europe and attracts visitors from all over the world for its wildlife viewing and natural landscape. With this development and anthropogenic influence comes concern for the well being of whales that migrate to the bay for its rich feeding opportunities. A code of conduct was established by a group of local whale watching operators that seek to provide management and sustainable practices in the industry to limit harmful impacts to cetaceans. This study aims to identify any disturbances to the behaviour of humpback whales in Skjálfandi Bay in the presence of vessels and assess compliance to the code of conduct regulations. Data was collected for three months from July-September 2019 on board a whale watching vessel where measurements such as vessel speed, distance to whale, number of boats during an encounter and general behaviour of whales were recorded. Results found no significant changes in diving behaviour of humpback whales when in the vicinity of whale watching vessels when dive time was correlated with number of boats, vessel speed and distance to whale. A kruskal-wallis test revealed a significant relationship between surface number and directness index (p-value 0.02), indicating that swimming patterns of whales changed as an encounter progressed and that whales respond to vessel presence progressively rather than immediately. Compliance with the code of conduct was adhered to for distance to whale but varied in length of encounters and speed restraints each month, due to fewer whales in the area and pressure on captains. Future long-term studies should continue to monitor whale watching activities in Skjálfandi Bay and stricter enforcement on the code of conduct should be applied. Hvalaskoðun er orðinn iðnaður með meira en milljarð dollara hagnað um ...